GW24-e3724 Comparison of the SinoSCORE and the EuroSCORE for predicting in-hospital mortality in patients undergoing coronary artery bypass Grafting. (1st October 2013) - Pin-Ming, Liu; Xi-Mei, Sang; Gui-Yi, Yuan; Ping, Hua; Yan-Qi, Yang; Jing-Feng, Wang
Abstract : Objectives: The European System for Cardiac Operative Risk Evaluation (EuroSCORE) is a commonly used risk model worldwide for the predicting mortality after cardiac surgery and the Sino System for Coronary Operative Risk Evaluation (SinoSCORE) is a new risk stratification model developed using Chinese multicentre database. We compared the Sinoscore and the Euroscore with regard to their validity to predict in-hospital mortality after coronary coronary bypass grafting (CABG) in a single-centre patient population of China. Methods: Detailed data for the EuroSCORE and the SinoSCORE risk factors were collected for 386 patients undergoing CABG or CABG combined other cardiac surgery at this institution between January 2006 and December 2012. All patients were scored according to the additive EuroSCORE and the SinoSCORE model respectively, and the mortality probability for individual patient was derived using these two models. The patients were divided into low-, intermediate-, and high-risk group according to the risk score results. Predicted mortality was compared to observed mortality for each risk category. Model discrimination was obtained using the area under the receiver operating characteristics (ROC) curve and calibration of the two risk models was assessed by the Hosmer-Leme show goodness-of-fit test. Results: According to EuroSCORE, 51.3% (198/386), 30.1% (116/386), and 18.7% (72/386) patients were in the low-risk, intermediate-risk and high-risk group respectively; predicted mortality was 1.2% for the low-risk, 3.6% for the intermediate-risk, 6.7% for high-risk group. Actual mortality was 2.8%, 7.9% and 20.2% among the three groups respectively. Area under the ROC curve was 0.755. Hosmer-Lemeshow of fit test showed P = 0.037. According to SinoSCORE, 28.7% (111/386), 30.6% (118/386), and 40.7% (157/386) patients were in the low-risk, intermediate-risk, and high-risk group respectively; predicted mortality was 0.9% for low-risk, 2.4% for intermediate-risk, and 16.6% for high-risk group. Actual mortality was 3.3%, 4.7% and 16.5% among the three groups respectively. Area under the ROC curve of SinoSCORE was 0.783. Hosmer-Lemeshow of fit test showed P = 0.614. Conclusions: Both the Euroscore and the Sinoscore have acceptable discriminatory ability in predicting in-hospital mortality in patients undergoing CABG; whereas, the SinoSCORE gives a more accurate prediction for the high-risk patients.